(Dis)care: Body, Speed and Dematerialization - Bonavitta , Paola (2024)
This essay examines autoethnography as a way of understanding the world. Thus, and committed to a science that prioritizes the body and disputes traditional senses of positivist work. It takes into account the epistemic privilege of the feminist point of view. We also start from an epistemology of affections and emotions, which places life itself at the center. From there, we discuss about and about an ethics of care, focusing on maternity as a political act, as a transforming action that confronts, in some way, the permanent demand of the capitalist system. Motherhood, as an institution not subservient to power, does not exist as such; however, we inhabit our bodies integrally of their capacities and potencies, which allows us to make this institution a daily weaving.